Investigating the effects of concentrate supplement level and type on milk fat production and animal performance of spring-calving grazing dairy cows - C. Heffernan; T.F. O'Callaghan; R. Fitzgerald; E. Serra; M. Frizzarin; N. Galvin; D.T. Mannion; K.N. Kilcawley; J.A. O'Mahony; M. Dineen (Journal of Dairy Science)
ABSTRACT: The objective of this experiment was to investigate the effect of concentrate supplement level and type on the milk fat production of grazing dairy cows in early to mid-lactation during a high-risk period for reduced milk fat synthesis. Eighty Holstein Friesian dairy cows averaging (mean ± SD) 55 ± 14 DIM were blocked based on their pre-experimental milk production and parity and randomly assigned to 1 of 5 dietary treatments: a pasture-only (P) control supplemented with 0.27 kg of DM/cow per day of a mineral and vitamin pack (P0); P supplemented with 2 kg of DM/cow per day of an industry-standard concentrate (P2); P supplemented with 4 kg of DM/cow per day of an industry-standard concentrate (P4); P supplemented with 4 kg of DM/cow per day of a concentrate containing 10% sodium hydroxide-treated straw (P4S); and P supplemented with 4 kg of DM/cow per day of a concentrate containing 5% calcium salts of fatty acids (P4F). The experiment consisted of an initial 2-wk covariate period, 1 wk of diet acclimatization, and a 12-wk period of data collection. Concentrate supplement level and type had no effect on milk fat concentration. Increasing the concentrate supplementation level linearly increased milk yield, ECM yield, fat yield, protein yield, lactose yield, and milk solids yield. Cows fed P4F had greater milk yield and lactose yield but lower milk protein concentration compared with cows fed P4 and P4S. Compared with the P4S diet, cows fed the P4F diet had greater milk fat yield and tended to produce greater milk solids yield. Cows fed P4F had lower proportions of de novo and mixed fatty acids (FA), as well as greater proportions of preformed FA compared with cows fed P4 and P4S. Cows fed P2 and P4 increased DM and OM intake compared with cows fed P0; however, cows fed P2 and P4 were similar. The total FA intake of cows fed P4 was greatest (400 g/d), cows fed P2 was intermediate (370 g/d), and cows fed P0 was lowest (330 g/d). Changing the concentrate type had no effect on the intakes of total DM, pasture DM, and OM. These results suggest that, although concentrate level and type can affect milk fat yield, they do not affect the milk fat concentration of grazing dairy cows within the conditions investigated in this experiment. Further research is required to determine the nutritional and non-nutritional factors responsible for reducing milk fat concentration in pasture-based systems during the high-risk period.